Covalent Linkage of BODIPY-Photosensitizers to Anderson-Type Polyoxometalates Using CLICK Chemistry - Cetindere, Seda; Clausing, Simon T.; Anjass, Montaha; Luo, Yusen; Kupfer, Stephan; Dietzek, Benjamin; Streb, Carsten (Chemistry - A European Journal, 2021)
The covalent attachment of molecular photosensitizers (PS) to polyoxometalates (POMs) opens new pathways to PS-POM dyads for light-driven charge-transfer and charge-storage. Here, we report a synthetic route for the covalent linkage of BODIPY-dyes to Anderson-type polyoxomolybdates by using CLICK chemistry (i. e. copper-catalyzed azide-alkyne cycloaddition, CuAAC). Photophysical properties of the dyad were investigated by combined experimental and theoretical methods and highlight the role of both sub-components for the charge-separation properties. The study demonstrates how CLICK chemistry can be used for the versatile linkage of organic functional units to molecular metal oxide clusters.
CRIS-Team Scopus Importer:2021-10-08
Keywords: BODIPY; organo-functionalization; photophysics; polyoxometalates; self-assembly

Expanding the Chemical Space of Tetracyanobuta-1,3-diene (TCBD) through a Cyano-Diels-Alder Reaction: Synthesis, Structure, and Physicochemical Properties of an Anthryl-fused-TCBD Derivative - Mateo, Luis M.; Sagresti, Luca; Luo, Yusen; Guldi, Dirk Michael; Torres, Tomas; Brancato, Giuseppe; Bottari, Giovanni (Chemistry - A European Journal, 2021)
Tetracyanobuta-1,3-diene (TCBD) is a powerful and versatile electron-acceptor moiety widely used for the preparation of electroactive conjugates. While many reports addressing its electron-accepting capability have appeared in the literature, significantly scarcer are those dealing with its chemical modification, a relevant topic which allows to broaden the chemical space of this interesting functional unit. Here, we report on the first example of a high-yielding cyano-Diels-Alder (CDA) reaction between TCBD, that is, where a nitrile group acts as a dienophile, and an anthryl moiety, that is, acting as a diene. The resulting anthryl-fused-TCBD derivative, which structure was unambiguously identified by X-ray diffraction, shows high thermal stability, remarkable electron-accepting capability, and interesting electronic ground- and excited-state features, as characterized by a thorough theoretical, electrochemical, and photophysical investigation. Moreover, a detailed kinetic analysis of the intramolecular CDA reaction transforming the anthryl-TCBD-based reactant into the anthryl-fused-TCBD product was carried out at different temperatures.
CRIS-Team Scopus Importer:2021-10-22
Keywords: anthryl-fused derivative; cyano-Diels-Alder reaction; electron acceptor; photophysics; tetracyanobuta-1; 3-diene

Synthesis, physicochemical properties and theoretical calculations of a subphthalocyanine peripherally substituted by multiple anthryl-ethynyl-aniline moieties - Fernandez-Vera, Oscar; Bo, Yifan; Luo, Yusen; Labella, Jorge; Guldi, Dirk Michael; Torres, Tomás; Bottari, Giovanni (Journal of Porphyrins and Phthalocyanines, 2023)
We report here the synthesis of a novel C3-subphthalocyanine (SubPc)-based electron donor-acceptor conjugate (1) in which the macrocycle has been functionalized at its peripheral positions with three anthryl-ethynyl-N,N-dimethylaniline groups. The latter moiety, besides conferring increased stability and solubility to the resulting system, substantially broadens its absorption capability. In-depth spectroscopic, spectrometric, and electrochemical analyses as well as theoretical calculations carried out on 1 suggest a moderate ground state intramolecular interaction between the macrocycle and the orthogonally-arranged anthryl-ethynyl-N,N-dimethylaniline moieties. Interestingly, such electronic communication significantly increases in the excited state in a process strongly depending on the polarity of the solvent. On the one hand, in toluene, upon photoexcitation of the anthryl-ethynyl-aniline, the formation of a 1*(SubPc) state is observed which decays into a 3*(SubPc) manifold before deactivating to the ground state. On the other hand, increasing the polarity of the solvent to tetrahydrofuran and benzonitrile, significantly modifies the fate of the photoexcited state. In this new scenario, the 1*(SubPc) state, formed directly upon 550 nm light stimulation or by 1*(anthryl-ethynyl-aniline) sensitization upon 405 nm excitation, transforms into a charge transfer (SubPc)d–-anthryl-ethynyl-anilined+ state which further evolves into a fully charge-separated (SubPc)•−-anthryl-ethynyl-aniline•+ species before deactivating to the ground state.
CRIS-Team Scopus Importer:2023-12-22
Keywords: aniline; anthryl moiety; panchromaticity; photophysics; subphthalocyanine